Synthetic ACTH for Treatment of Glomerular Diseases: A Case Series. (January 2022) - Jauhal, Arenn; Prasad, Bhanu; Rousseau-Gagnon, Mathieu; Ouellet, Gabriel; A Hladunewich, Michelle
Rationale: Synthetic adrenocorticotropic hormone (Tetracosactide) has been used in the treatment of refractory glomerular diseases. Literature surrounding the use of this medication is limited to small case series and there is conflicting data on the rate of adverse events associated with this medication. Presenting concerns of the patient: Glomerulonephritis not in remission after at least 6 months of treatment with conservative care. Stable doses of concurrent immunosuppression were permitted. Diagnoses: Membranous nephropathy, IgA nephropathy, minimal change disease, and focal and segmental glomerulosclerosis. Intervention: Intramuscular synthetic adrenocorticotropic hormone (Tetracosactide, Synacthen Depot) with doses of either 1 mg weekly or 1 mg twice weekly. Outcomes: Five of 12 patients had at least a partial remission with Tetracosactide. Median time to response was 6 months for responders. Five of the 12 patients had adverse events documented, 2 of which led to treatment discontinuation. No patients with focal and segmental glomerulosclerosis responded to treatment. Lessons Learned: Higher rate of adverse events than previously reported with synthetic adrenocorticotropic hormone and uncertain treatment efficacy.